Business and Livelihoods in African Livestock : Investments to Overcome Information Gaps - World Bank (Washington, DC, 2014)
This paper investigates how the development of the livestock sector can contribute to economic growth and poverty reduction in the continent, with the ultimate objective of identifying major information gaps critical to designing and implementing successful livestock sector policies and investments. As a first step, the paper presents an analysis of African consumption of animal-source foods. This is rapidly growing and is forecast to continue doing so. It therefore provides opportunities for demand-led growth. This focus is distinct from the more traditional, production-oriented entry point. To understand opportunities for poverty reduction, this paper reviews both the quantitative and qualitative dimensions of African markets for livestock products, in this case animal-source foods. Second, rather than exploring production and productivity constraints, which are known to a large extent, the paper focuses on the incentives that rural households have to invest in their livestock to overcome those constraints. Indeed, farmers often fail to adopt readily available technologies. To analyze incentives, the paper reviews two intertwined dimensions of households' livestock activities, namely herd and flock size and livestock-derived income. The paper concludes by identifying investment priorities for improving the quantity and quality of livestock information so that decision makers will be better able to formulate and implement investments in the livestock sector that effectively contribute to economic growth and poverty reduction.